SURGICAL METHODS FOR THE RECONSTRUCTION OF MAXILLOFACIAL DEFORMITIES CAUSED BY TRAUMATIC INJURIES. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Traumatic injuries to the maxillofacial region often result in severe functional and aesthetic deformities, requiring advanced surgical intervention for proper reconstruction. This article explores modern surgical techniques used in the reconstruction of maxillofacial deformities caused by trauma, focusing on methods such as bone grafting, distraction osteogenesis, alloplastic implants, and 3D printing technology. Advances in microsurgery, virtual surgical planning (VSP), and computer-aided design and manufacturing (CAD/CAM) have improved precision and patient outcomes. Additionally, the article discusses challenges in post-surgical recovery, complications such as infection and graft failure, and the future prospects of regenerative medicine in maxillofacial reconstruction.